Zoledronic Acid Targeting of the Mevalonate Pathway Causes Reduced Cell Recruitment and Attenuates Pulmonary Fibrosis - Tanner, Lloyd; Bergwik, Jesper; Single, Andrew B.; Bhongir, Ravi K. V.; Erjefält, Jonas S.; Egesten, Arne (Frontiers in Pharmacology, 2022)
Background and aim: Idiopathic pulmonary fibrosis (IPF) is a progressive lung disease causing irreparable scarring of lung tissue, with most patients succumbing rapidly after diagnosis. The mevalonate pathway, which is involved in the regulation of cell proliferation, survival, and motility, is targeted by the bisphosphonate zoledronic acid (ZA). The aim of this study was to assess the antifibrotic effects of ZA and to elucidate the mechanisms by which potential IPF treatment occurs. Methods: A series of in vitro and in vivo models were employed to identify the therapeutic potential of ZA in treating IPF. In vitro transwell assays were used to assess the ability of ZA to reduce fibrotic-related immune cell recruitment. Farnesyl diphosphate synthase (FDPS) was screened as a potential antifibrotic target using a bleomycin mouse model. FDPS-targeting siRNA and ZA were administered to mice following the onset of experimentally-induced lung fibrosis. Downstream analyses were conducted on murine lung tissues and lung fluids including 23-plex cytokine array, flow cytometry, histology, Western blotting, immunofluorescent staining, and PCR analysis. Results: In vitro administration of ZA reduced myofibroblast transition and blocked NF-κB signaling in macrophages leading to impaired immune cell recruitment in a transwell assay. FDPS-targeting siRNA administration significantly attenuated profibrotic cytokine production and lung damage in a murine lung fibrosis model. Furthermore, ZA treatment of mice with bleomycin-induced lung damage displayed decreased cytokine levels in the BALF, plasma, and lung tissue, resulting in less histologically visible fibrotic scarring. Bleomycin-induced upregulation of the ZA target, FDPS, was reduced in lung tissue and fibroblasts upon ZA treatment. Confirmatory increases in FDPS immunoreactivity was seen in human IPF resected lung samples compared to control tissue indicating potential translational value of the approach. Additionally, ZA polarized macrophages towards a less profibrotic phenotype contributing to decreased IPF pathogenesis. Conclusion: This study highlights ZA as an expedient and efficacious treatment option against IPF in a clinical setting.